Anti-Corruption Behavior: Its Relationship to The Creation of Food Independence and Community Welfare In 3T Regions - Raden Roro Atiqah Sekararum; Baren Sipayung; Selvia Junita Praja; Rabith Madah Khulaili Harsya; Mitra Musika Lubis (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study aims to analyze the influence of anti-corruption behavior on food self-sufficiency and its impact on community welfare in the Frontier, Outermost, and Disadvantaged (3T) regions. Corruption in the distribution of food aid and agricultural subsidies is often a major obstacle to the development of remote areas. Using a qualitative approach and in-depth literature review, this study explores how the integrity of local governance can ensure the effectiveness of food security programs. The analysis shows that anti-corruption behavior, manifested through budget transparency and public accountability, contributes significantly to sustainable food availability. The resulting food self-sufficiency ultimately becomes a key determinant in improving the welfare standards of communities in the 3T regions. This study recommends strengthening community-based supervision and digitizing the bureaucracy to minimize rent-seeking practices in the food sector in disadvantaged areas.